2016
DOI: 10.1096/fj.201600826r
|View full text |Cite
|
Sign up to set email alerts
|

RANKL induces Bach1 nuclear import and attenuates Nrf2‐mediated antioxidant enzymes, thereby augmenting intracellular reactive oxygen species signaling and osteoclastogenesis in mice

Abstract: Reactive oxygen species (ROS) play a role in intracellular signaling during osteoclastogenesis. We previously reported that transcriptional factor nuclear factor E2-related factor 2 (Nrf2) was exported from the nucleus to the cytoplasm by receptor activator of nuclear factor-κB ligand (RANKL), and that Nrf2 negatively regulated osteoclastogenesis via antioxidant enzyme up-regulation. Knockout mice of BTB and CNC homology 1 (Bach1)-the competitor for Nrf2 in transcriptional regulation-was known to attenuate RAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 41 publications
4
53
0
Order By: Relevance
“…Indeed, RANKL stimulation decreases expression of NRF2-dependent cytoprotective enzymes, thereby facilitating intracellular ROS signaling (Kanzaki et al, 2013, 2016b). Induction of cytoprotective enzymes by NRF2 activation subsequently inhibits osteoclastogenesis (Kanzaki et al, 2013, 2014, 2015; Sakai et al, 2013; Gambari et al, 2014; Lee et al, 2014; Lu et al, 2015; Bhattarai et al, 2016).…”
Section: Mechanisms That Protect Against Oxidative Stressmentioning
confidence: 99%
“…Indeed, RANKL stimulation decreases expression of NRF2-dependent cytoprotective enzymes, thereby facilitating intracellular ROS signaling (Kanzaki et al, 2013, 2016b). Induction of cytoprotective enzymes by NRF2 activation subsequently inhibits osteoclastogenesis (Kanzaki et al, 2013, 2014, 2015; Sakai et al, 2013; Gambari et al, 2014; Lee et al, 2014; Lu et al, 2015; Bhattarai et al, 2016).…”
Section: Mechanisms That Protect Against Oxidative Stressmentioning
confidence: 99%
“…In response to oxidative stress, Keap1‐interactors displace Nrf2, which then migrates into the nucleus and binds the antioxidant response element (ARE) in the promoter of its target genes, as a heterodimer with small Maf proteins . Another transcription factor (BTB and CNC homology 1, Bach1) is involved in transcriptional regulation as a Nrf2 competitor and is shuttled in and out of the nucleus to respectively attenuate or liberate Nrf2 activity in response to different stimuli . Reduced Nrf2 activity has been linked to a number of pathological conditions .…”
Section: Introductionmentioning
confidence: 99%
“…(10) Another transcription factor (BTB and CNC homology 1, Bach1) is involved in transcriptional regulation as a Nrf2 competitor and is shuttled in and out of the nucleus to respectively attenuate or liberate Nrf2 activity in response to different stimuli. (11,12) Reduced Nrf2 activity has been linked to a number of pathological conditions. (13)(14)(15)(16)(17)(18) Furthermore, alterations of the Keap1/Nrf2 pathway have been reported in animal models of bone disease, and lack of Nrf2 exacerbated pathological phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that Nrf2 was transiently down‐regulated during osteoclastogenesis . In these studies, we also found that overexpression of Nrf2 inhibited osteoclastogenesis, and knockdown of Nrf2 induced osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 62%